Delivery balloon volume positively correlates with the diameter and effective orifice area of implanted SAPIEN 3. Issue 3 (September 2022) - Nomura, Takehiro; Miyasaka, Masaki; Nakashima, Masaki; Saigan, Makoto; Inoue, Arata; Enta, Yusuke; Toki, Yusuke; Ishii, Kazunori; Sakurai, Mie; Munehisa, Yoshiko; Ito, Jun; Hata, Masaki; et al.
Abstract: Background: In transcatheter aortic valve replacement (TAVR) using SAPIEN 3 (S3) (Edwards Lifesciences, Irvine, CA, USA), some clinicians decrease or increase the delivery balloon volume (VOL) when deploying S3 or conducting post-dilatation. However, the effects of controlling VOL on transcatheter heart valve diameter (THVD) and valve function remain unclear. We assessed associations among VOL, THVD, and effective orifice area (EOA) of S3. Methods: We enrolled patients undergoing TAVR using 23- and 26-mm S3 in Sendai Kousei Hospital between 2017 and 2019. VOL was controlled based on preprocedural computed tomography and intraprocedural transesophageal echocardiography (TEE). THVD were defined as the diameters of transcatheter heart valve at mid-level measured by TEE. Results: In enrolled 332 patients (23-mm, n  = 188; 26-mm, n  = 144), one (0.3%) and two (0.6%) developed annulus rupture and moderate/severe paravalvular leak, respectively. VOL at deployment was positively correlated with THVD on deployment (23-mm, r  = 0.44, p  < 0.001; 26-mm, r  = 0.57, p  < 0.001) and EOA (23-mm, r  = 0.23, p  = 0.0019; 26-mm, r  = 0.22, p  = 0.0094). In multiple regression analyses, VOL and post-dilatation were significant determinants of THVD, although aortic annulus area, calcium volume, and pre-dilatation were not. The areas under the receiver operating characteristic curve that were used to evaluate the accuracy of the index obtained by dividing THVD by body surface area (indexed THVD) to predict patient–prosthesis mismatch (PPM) were 0.744 and 0.811 in the 23- and 26-mm cohorts, respectively. A cut-off indexed THVD of ≤11.5 and 12.1 mm/m 2 well predicted PPM (23-mm, odds ratio, 5.20; 95% confidence interval, 1.33–20.3; 26-mm, odds ratio 14.1, 95% confidence interval 2.40–81.0). Conclusion: VOL was positively correlated with THVD and EOA. Smaller indexed THVD was associated with a higher incidence of PPM. Controlling VOL under on-site THVD evaluation may be useful in reducing the PPM incidence. Graphical abstract: Unlabelled Image Highlights: A balloon volume was correlated with valve diameter and effective orifice area in transcatheter aortic valve replacement (TAVR) using SAPIEN3. Post-dilatation was a significant determinant of valve diameter in TAVR using SAPIEN3. A smaller indexed diameter (diameter/body surface area) may lead to a higher patient–prosthesis mismatch (PPM) incidence. Controlling balloon volume and post-dilatation may reduce the incidence of PPM. Measuring transcatheter heart valve diameter during TAVR procedure may be useful to control balloon volume.